Response of Three Cereal Crops to Different Clipping Times for Forage Yield at two Locations of Sulaimani Region - Tawfiq, SH. E.; Muhammed, S. R. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The present study was conducted in Sulaimani Region at two different locations, Qlyasan and Kanipanka during the winter season of 2010-2011, to estimate the response of three cereal crops each with three varieties namely, wheat (Cham-6, Tammuz-2, IPA-95), barley (Amal-2, Arivat, IPA-99), and triticale (Eronga, Clossbied, Ruaida) to different clipping times{clipping 80 days after sowing (clipping time1), clipping 90 days after sowing (clipping time 2), clipping 100 days after sowing (clipping time 3), and clipping 110 days after sowing (clipping time 4) as well as control (no clipping)} for Qlyasan location and the following day at Kanipanka location. The design was split plot within factorial experiment, the varieties implemented in the main plots and arranged with complete randomized design (CRBD) and replicated three times, where the clipping times implemented in sub plots. Means comparison were carried out using least significant difference test (LSD) at 0.05 significant level. The results of the present study can be summarized as follow: IPA-99 barley variety exhibited superior values for the characters: fresh and dry yield, while IPA-95 wheat variety and Eronga triticale variety gave maximum value of dry matter%. The fourth clipping time exceeded the other clipping times in the characters: Fresh, dry yield and dry matter% with 16.706, 3.126 and 18.959 respectively. Kanipanka location produced maximum values for the characters: Fresh, dry yield and dry matter% in compare to Qlyasan location.
Keywords: Forages clipping times varieties fresh yield dry yield dry matter